Inspire Challenge Award: Real-time diagnostics for devastating wheat rust - CGIAR Platform for Big Data in Agriculture (2018)
Demonstrated that a small gene sequencing device could be used in the field to identify a strain of wheat rust within 48 hours, dramatically reducing the response cycle time. The pilot demonstrated the first-ever accurate identification of individual yellow rust strains just as the disease emerged in the field.